Development of the anterior visual input pathway to the Drosophila central complex. - Lovick, J.K.; Omoto, J.J.; Ngo, K.T.; Hartenstein, V. (Journal of Comparative Neurology, 2017)
The anterior visual pathway (AVP) conducts visual information from the medulla of the optic lobe via the anterior optic tubercle (AOTU) and bulb (BU) to the ellipsoid body (EB) of the central complex. The anatomically defined neuron classes connecting the AOTU, BU, and EB represent discrete lineages, genetically and developmentally specified sets of cells derived from common progenitors (Omoto et al., Current Biology, 27, 1098-1110, 2017). In this article, we have analyzed the formation of the AVP from early larval to adult stages. The immature fiber tracts of the AVP, formed by secondary neurons of lineages DALcl1/2 and DALv2, assemble into structurally distinct primordia of the AOTU, BU, and EB within the late larval brain. During the early pupal period (P6-P48) these primordia grow in size and differentiate into the definitive subcompartments of the AOTU, BU, and EB. The primordium of the EB has a complex composition. DALv2 neurons form the anterior EB primordium, which starts out as a bilateral structure, then crosses the midline between P6 and P12, and subsequently bends to adopt the ring shape of the mature EB. Columnar neurons of the central complex, generated by the type II lineages DM1-4, form the posterior EB primordium. Starting out as an integral part of the fan-shaped body primordium, the posterior EB primordium moves forward and merges with the anterior EB primordium. We document the extension of neuropil glia around the nascent EB and BU, and analyze the relationship of primary and secondary neurons of the AVP lineages.